Introduction: Social Work & Society - A Glossary for Theory and Practice - Fabian Kessl (Social Work & Society, 2006)
Social Work & Society (SW&S) is an Online-Only Journal on Social Work and Social Policy, which was founded in 2003. SW&S is based on an international, non-governmental network of Social Work and Social Policy Researchers and Teachers. SW&S opens up an independent platform for critical analyses, political discourses and informations on current developments in Social Work and Social Policy. SW&S is also of the International Open Access Initiative and therefore all papers and informations are free available for all SW&S-users. To widen the possibilities for the users, SW&S starts in 2006 a SW&S-Glossary on Social Work and Social Policy (Issue 6).